1990
DOI: 10.1002/job.4030110504
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of organizational commitment: Methodological investigation

Abstract: Extensive research on the consequences of organizational commitment (OC) has been conducted over the past decade. The purpose of this paper is to summarize empirical evidence about the relationship between OC and work outcomes and to examine the effect of methodological decisions on the OC–work outcome relationship. A meta‐analysis of 35 studies of the OC–work outcome linkage reveals that the overall empirical relationship between OC and outcome variables is generally weak, but positive. While subgroup analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
3
20

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(190 citation statements)
references
References 60 publications
(83 reference statements)
6
158
3
20
Order By: Relevance
“…Many studies (Randall, 1990;Shore et al, 1990;Tett & Meyer, 1993) show that intention to leave is the most evident indicator of one's actually leaving their job. Chang et al (2013) carried out studies to find out reasons for leaving one's job and concluded that the most referenced reasons for leaving one's job are work autonomy, fair reward, social support, job satisfaction, organizational commitment, tenure, and demographic features like age-gender.…”
Section: Perceived Organizational Support As a Mediatormentioning
confidence: 99%
“…Many studies (Randall, 1990;Shore et al, 1990;Tett & Meyer, 1993) show that intention to leave is the most evident indicator of one's actually leaving their job. Chang et al (2013) carried out studies to find out reasons for leaving one's job and concluded that the most referenced reasons for leaving one's job are work autonomy, fair reward, social support, job satisfaction, organizational commitment, tenure, and demographic features like age-gender.…”
Section: Perceived Organizational Support As a Mediatormentioning
confidence: 99%
“…Different studies show the relationship between organizational commitment and individual-level outcomes (performance, turnover and absenteeism) and organizational level (organizational effectiveness) (Cohen, 1993;Randall, 1990). Therefore, the analysis of identification and commitment as carried out within the frame of the HSA is of special benefit and added value for health care organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews (e.g. Mathieu and Jajac 1990;Randall 1990) mentioned that organizational commitment may be conceptualized in various ways. Meyer et al (1990) identified two types of organizational commitment: affective commitment and continuance commitment.…”
Section: Procedural Fairness and Managerial Performancementioning
confidence: 99%